Metodika stanovení nákladů na zdravotně technické instalace v nižších stupních dokumentace - Zanáška, Filip (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Bakalářská práce se zabývá cenami ve stavebnictví. Cílem práce je vytvořit metodiku na stanovení ceny vnitřních zdravotně technických instalací. Teoretická část popisuje ceny ve stavebnictví a jejich tvorbu. Praktická část obsahuje popis tvorby metodiky a možný postup pro získání ceny.

The bachelor thesis deals with prices in construction. The aim of the work is to create a methodology for determining the price of internal sanitary installations. The theoretical part describes prices in construction and their creation. The practical part contains a description of the creation of the methodology and a possible procedure for obtaining the prize.
Methodology for determining the costs of sanitary installations in lower levels of documentation
Keywords: Cena; ceny ve stavebnictví; zdravotně technické zařízení; kanalizace; vodovod; zařizovací předměty; obestavěný prostor; podlahová plocha; zastavěná plocha; Price; prices in construction; sanitary equipment; sewerage; water conduit; sanitary; enclosed area; floor area; build up area